Pengawasan Dalam Proses Penyusunan Dan Pelaksanaan Anggaran - Asman Barhani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The phenomenon of low public participation in the budget preparation process causes the income and expenditure budget which should be the rights of the people to actually benefit the bureaucracy (the rulers) more in the author's opinion, is a form of secularization of accounting (budgeting). Secularization according to Glasner (1992, 65) relies on Comte's idea of positivism, which emphasizes knowledge solely on empirical observations of data that can be sensed. In fact, in the budget preparation process, community participation is still low so that the programs and activities proposed by the community are very minimally funded in the budget. Even though the budget comes from taxes, levies and other income that comes from the people